Empirical testing of an information systems evaluation framework. (19th April 2004) - Irani, Z.
The justification of information technology (IT) and information systems (IS) is inherently complex, since there are a large range of benefits that are intangible and non-financial, which thus present much difficulty during investment appraisal. However, it is not only the benefits of IT/IS that present this difficulty but also the range of indirect costs associated with an IT/IS deployment. Therefore, many justification processes are often exclusively based on those financially tangible benefits and costs that can be accounted for within traditional appraisal techniques. This paper describes the testing of a novel framework for the evaluation of IT/IS in manufacturing, with a particular focus on manufacturing resource planning (MRPII). This proposed approach addresses many of the limitations inherent in traditional appraisal techniques. The testing of this framework is then carried out through describing a case experience of a small/medium enterprise (SME) that was unable to "fully" justify its capital expenditure on MRPII, whilst using traditional approaches to financial appraisal. As a result of their inability to financially justify their expenditure, the company adopted a simple cost/benefit analysis, and invested as an "act of faith". The author describes the idiosyncrasies of the case study company, and details the problems experienced during his attempts to evaluate, implement and realise the holistic implications of their MRPII investment. Although the IS was operational for a period of time, it was eventually deemed a failure, due to a range of human and organisational issues. This paper identifies those factors, and describes how the company addressed them before embarking on a process of bespoke system development and implementation. The author then tests the proposed hypotheses, which underpin the constructs within the previously presented IT/IS evaluation framework, against both vendor purchased software and a bespoke developed system